Congenital malformations of the bile ducts - Taibo Canale, Walter (Cirugía del Uruguay, 1975)
The most frequent congenital anomalies of the bile ducts: biliary atresia and choledocus cyst, are studied. A revision of the literature is pointed out. It is hoped there will be an improvement in the treatment of these lesions, based on the results obtained by the Japanese School.